2005
DOI: 10.1111/j.1945-5100.2005.tb00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Target rocks, impact glasses, and melt rocks from the Lonar impact crater, India: Petrography and geochemistry

Abstract: Abstract-The Lonar crater, India, is the only well-preserved simple crater on Earth in continental flood basalts; it is excavated in the Deccan trap basalts of Cretaceous-Tertiary age. A representative set of target basalts, including the basalt flows excavated by the crater, and a variety of impact breccias and impact glasses, were analyzed for their major and trace element compositions. Impact glasses and breccias were found inside and outside the crater rim in a variety of morphological forms and shapes. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 30 publications
6
106
3
Order By: Relevance
“…See Reimold 2007) impact structures known on Earth, but the well-studied, 1.8 km in diameter Lonar structure (e.g., Fredriksson et al 1973;Osae et al 2005) in Maharashtra (central India) is until now the only confirmed impact structure in the entire region of the Indian subcontinent and Far East Asia. Besides Lonar, the so-called Ramgarh structure, an ∼4 km wide crater-like feature in Rajasthan (Master and Pandit 1999;Sisodia et al 2006), and the proposed Shiva structure in the Arabian Sea to the southwest of the Indian subcontinent (Chatterjee et al 2006), have been suggested as being of possible impact origin.…”
Section: Introductionmentioning
confidence: 99%
“…See Reimold 2007) impact structures known on Earth, but the well-studied, 1.8 km in diameter Lonar structure (e.g., Fredriksson et al 1973;Osae et al 2005) in Maharashtra (central India) is until now the only confirmed impact structure in the entire region of the Indian subcontinent and Far East Asia. Besides Lonar, the so-called Ramgarh structure, an ∼4 km wide crater-like feature in Rajasthan (Master and Pandit 1999;Sisodia et al 2006), and the proposed Shiva structure in the Arabian Sea to the southwest of the Indian subcontinent (Chatterjee et al 2006), have been suggested as being of possible impact origin.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the Bunburra meteorite has well-developed crystals of pyroxene and plagioclase up to hundreds of microns long, which contrast with the aphyric Lonar melt rocks (Osae et al, 2005). The crystalline nature of Bunburra indicates much slower cooling (and hence, a larger impact) as compared to Lonar, and is instead similar to the texture of the noritic impact melt of the Sudbury basin (Therriaut et al, 2002).…”
Section: Hypothesis 2: Complete Melting Of a Basaltic Target Rockmentioning
confidence: 98%
“…Addopting the volume of the Deccan magma (1.2 × 10 6 km 3 ) estimated by Keller et al [15], a simple calculation shows that approximately 1 × 10 6 km 3 or 3 × 10 21 g of basaltic lava (assumed density: 3 g cm -3 ) erupted during the most active phase-2 of the Deccan eruptions. Osae et al [38] carried out geochemical analyses major oxides and trace elements, including As (and Ir), of numerous target basalt samples from the Lonar impact crater; this crater is escavated in the KPB basalts of Deccan. They reported that average concentrations of As and Ir in their samples is 0.58 ppm and <1ppb, respectfully.…”
Section: Deccan Trapsmentioning
confidence: 99%